Development, Test and Validation of a Mechatronic Device for Spasticity Quantification. (29th May 2013) - Ferreira, João F.; Moreira, Vitor; Lima, Carlos S.; Soares, Filomena; Machado, José; Leão, Celina P.
Abstract Spasticity is a common pathological phenomenon in clinical practices, frequently expressed as a stroke, multiple sclerosis or cerebral palsy. The accurate quantification of spasticity allows early action to prevent the potentially irreversible consequences. The aim of this work is to develop and implement a mechatronic device for the accurate quantification of spasticity, which is able to differentiate spasticity from other motor disorders. The proposed method is based on the quantification of the tonic stretch reflex threshold (TSRT) for the assessment of the range of motion of the limb affected by spasticity. In order to validate the developed device, experimental trials have been conducted, considering the flexor muscle of the elbow joint. The developed device was tested, first in a laboratory environment with healthy subjects and secondly, in a clinical environment with the collaboration of patients with spasticity. The evaluations in th clinical environment were performed on three different days in order to evaluate the reproducibility of the obtained results. The experimental trials confirm the sensibility, reproducibility and reliability of spasticity quantification based on the TSRT method. This project has been developed in cooperation with the Hospital of Braga and Fisimaia rehabilitation clinic, both in Portugal.